2014
DOI: 10.1016/j.sbspro.2014.07.313
|View full text |Cite
|
Sign up to set email alerts
|

The International Tourists’ Perspective on Malaysia's Economic Transformation Programme (ETP)

Abstract: The Economic Transformation Programme (ETP) is a strategic plan by the Malaysian Government to transform the tourism sector into a high-yield industry by 2020. It is vital to understand the perception of international tourists on the Government's initiatives in transforming the industry. Hence, this study aims to explore the international tourists' perception on transformation of the Malaysian tourism industry based on Malaysia's ETP. A practical insight of the characteristics of the Malaysian tourism industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Apparently, citizens' needs and wants is keep on changing due to time and socio-cultural advancement which makes municipal councils administrators faced different challenges [66,44]. These results oppose the assertions that finances are the main problems municipal councils in Malaysia were encountered with [67,43], but most countries of the world most especially developing countries were faced with financial crisis to discharged their statutory functions [68]. The results of this research also revealed that quality municipal services have an effect on citizen satisfaction as supported [7].…”
Section: Discussion Of Resultsmentioning
confidence: 93%
“…Apparently, citizens' needs and wants is keep on changing due to time and socio-cultural advancement which makes municipal councils administrators faced different challenges [66,44]. These results oppose the assertions that finances are the main problems municipal councils in Malaysia were encountered with [67,43], but most countries of the world most especially developing countries were faced with financial crisis to discharged their statutory functions [68]. The results of this research also revealed that quality municipal services have an effect on citizen satisfaction as supported [7].…”
Section: Discussion Of Resultsmentioning
confidence: 93%
“…According to Nair et al (2014), the government had allocated RM243 million for replanting programmes for cocoa, forest, oil palm, and rubber. Besides that, another RM15 million was also allocated for launching grants to establish a Malaysian Green Foundation to promote the use of green technology in the corporate sector.…”
Section: Problem Statementmentioning
confidence: 99%
“…The main objective of the current study is to determine if tourism in Malaysia should depend on eWOM or not. It is crucial to reposition tourism in Malaysia as our close neighbors such as Singapore and Thailand have improved the competitiveness and attractiveness of their tourism industry plans (Nair et al, 2014).…”
Section: Introductionmentioning
confidence: 99%